Lumpur Limbah Industri Alkohol sebagai Penyusun Konsentrat Pakan Domba - Damaryanto Widharto; Edy Rianto; Agung Purnomoadi (Universitas Sebelas Maret, 2005)
The present study was aimed to evaluate the use of ‘Lumpur-bahinol’ (sludge of alcohol industry) as feed for sheep on feed intake, daily gain, and feed conversion ratio. Twelve indigenous rams grouped into three consist of four were used in this study following Completely Randomized Design. Those rams were 8-10 months old, and average weight at 17,15 kg. The rams were raised in individual barn and were fed Napier grass ad libitum and commercial concentrate feed at 2% of body weight. The treatments were substitution of concentrate feed with ‘lumpur-bahinol’ in the rations at various level as follow, K5L0 (concentrate 2% BW+lumpur-bahinol 0% BW), K4L1 (Concentrate 1.6% BW+Lumpur-bahinol 0.4% BW) and K3L2 (concentrate 1.2% BW+Lumpur-bahinol 0.8% BW). These rations were adjusted to fulfill dry matter requirement at 4% BW. The result showed that inclusion of lumpur-bahinol in the ration tend to decrease total DMI (P=0.1105), being 815 and 809 g/d for K4L1 and K3L2m, respectively, compared to K5L0 (890 g/d). Similar tendency was observed in crude protein intake (P=0.1105), being 104,94 dan 92 g/d for K5L0, K4L1 and K3L2, respectively, as well as in gross energy intake (P=0.0999), being 13.3; 11.4 and 10.5 Mj/d, for K5L0, K4L1 and K3L2, respectively. This phenomena was in contrast with the digestibility that tend to increase (P=0.1056) as much as 0.96% (K4L1) and 2.80% (K3L2), respectively, compared to K5L0 (62.97%). Despite of feed intake tended to decrease as increasing lumpur-bahinol in concentrate, but the daily gain tend to be higher (P=0.1171) in K4L1 (65 g/d) and K3L2 (56 g/d) compared to K5L0 (53 g/d). Similar tendency was shown in feed conversion of K4L1 (12.5) and K3L2 (14.5) that better than of K5L0 (16.8). The conclusion of this study was lumpur-bahinol could be used to compose concentrate feeding up to 0.8% of body weight.